A Novel Proportional Multi-Resonant Current Controller Strategy for Reduced DC Voltage fed D-STATCOM with Internal LCL Resonance Damping - Satpathy Guddy; De Dipankar (Power Electronics and Drives, 2024)
This work focuses on a new topology-control-based D-STATCOM solution with reduced DC bus voltage requirement and with an excellent grid side performance. The proposed solution consists of a main inverter and auxiliary inverter along with a transformer and LCL filter network to achieve the required DC bus reduction. A new controller structure with two proportional-multi resonant controller for the converters with only one of the inductors current as a controlled variable ensures the active damping of the LCL resonance. The power circuit configuration assists the controller to generate a difference in the modulation signal due to non-equal gains in two controllers and helps to achieve the resonance damping without capacitor current sensor. Hence, the corresponding capacitor current sensor can be eliminated. The converter operates for any point of common coupling (PCC) loading conditions and the performance of the controller is immune to the grid impedance variation. A detailed stability study is carried out for the proposed controller. The proposed controller can achieve a very fast dynamic response with an excellent stability margin. The proposed solution is verified through simulation studies and through a scaled-down experimental prototype.